Improving Students' Writing Skills Through the Controlled to Free Approach with Do-It-Yourself (DIY) “Daily activities” - Geroda, Godefridus Bali; Rohman, Abdul; Nur , Dedi Rahman (Borneo Educational Journal (Borju), 2025)
The purpose of this research is to investigate the effectiveness of a blended pedagogical approach in improving students' writing skills. This approach combines a controlled-to-free writing method with engaging Do-It-Yourself (DIY) "Daily Activities" designed to enhance motivation and personalize the learning experience. Specifically, this study aims to determine if this integrated approach leads to significant improvements in students' writing proficiency, fluency, accuracy, and complexity compared to traditional writing instruction. This study used a Classroom Action Research (CAR) approach to address the practical challenges of improving students' writing skills through the controlled to free approach combined with DIY “Daily Activities.” The research showed that Post-test results showed a 25% improvement in students' writing scores compared to the pre-test. Specifically, grammar accuracy improved by 20%, coherence by 30%, and vocabulary usage by 25%. So, we can conclude that DIY "Daily Activities," is effective in improving students' writing skills.